Posture and gait in elderly [Yaşlilarda postür ve yürüme] - (:unkn) unknown (My University, 2000)
In the human aging process, many changes are seen in all the systems of the body. Posture, balance, and gait is also affected from the aging process. These changes are both related to disability and also are related to the increased risk of falls in the geriatric age group. Besides the advantages of erect posture, human beings have problems in the advanced age due to the disadvantages, like increased strain on the spine and lower extremities. Typical flexion posture is acquired in the advanced age. Body height decreases, dorsal kyphosis increases together with a decrease in cervical and lumbar lordosis. Shoulders droop and scapula is protracted. Hips and knees are in flexion. Fatty depots tend to disappear from the face and the periphery, although fat deposition is still apparent over the hips and the abdomen. Together with a change in the center of gravity, the plumb line of the body moves so that extension in lower extremity joints is no longer possible. A typical flexion posture is seen in patients with Parkinson's disease, which is quite common in the old age. Elderly people has balance problems both in maintaining the erect posture and also during walking. Some of the reasons are, decrease in sensory inputs and muscle power, increase in the latency of the postural responses and slowing of the postural reflexes. The dividing line between normal and abnormal may be difficult to define in the elderly people's gait. But senile gait, which is a label for unsteady gait of older persons that cannot be attributed to orthopedic and neurologic causes, is characterized by shorter stride length, wider walking base, increased step to step variability, slower walking speed, decrease in angular motion of the extremities and decrease in arm swings, and it is a secure walking pattern.
Keywords: Balance; Elderly. Aging; Gait; Posture